Birth of clones of the world's first cloned dog. Issue 1 (December 2017) - Kim, Min; Oh, Hyun; Kim, Geon; Setyawan, Erif; Choi, Yoo; Lee, Seok; Petersen-Jones, Simon; Ko, CheMyong; Lee, Byeong
Abstract Animal cloning has gained popularity as a method to produce genetically identical animals or superior animals for research or industrial uses. However, the long-standing question of whether a cloned animal undergoes an accelerated aging process is yet to be answered. As a step towards answering this question, we compared longevity and health of Snuppy, the world's first cloned dog, and its somatic cell donor, Tai, a male Afghan hound. Briefly, both Snuppy and Tai were generally healthy until both developed cancer to which they succumbed at the ages of 10 and 12 years, respectively. The longevity of both the donor and the cloned dog was close to the median lifespan of Afghan hounds which is reported to be 11.9 years. Here, we report creation of 4 clones using adipose-derived mesenchymal stem cells from Snuppy as donor cells. Clinical and molecular follow-up of these reclones over their lives will provide us with a unique opportunity to study the health and longevity of cloned animals compared with their cell donors.